2017
DOI: 10.1292/jvms.16-0658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total intravenous anesthesia with propofol-guaifenesin-medetomidine and alfaxalone-guaifenesin-medetomidine in Thoroughbred horses undergoing castration

Abstract: Anesthetic and cardiorespiratory effects of total intravenous anesthesia (TIVA) technique using propofol-guaifenesin-medetomidine (PGM) and alfaxalone-guaifenesin-medetomidine (AGM) were preliminarily evaluated in Thoroughbred horses undergoing castration. Twelve male Thoroughbred horses were assigned randomly into two groups. After premedication with intravenous (IV) administrations of medetomidine (5.0 µg/kg) and butorphanol (0.02 mg/kg), anesthesia was induced with guaifenesin (10 mg/kg IV), followed by eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…2 Aoki and others reported that the mean induction time in horses premedicated with medetomidine, butorphanol and guaifenesin followed by 1 mg/kg of alfaxalone was 49 seconds. 9 The characteristics of induction in our current study were similar to the results of these previous studies, and the 1 mg/kg of alfaxalone was considered to be an appropriate dose for the induction of anaesthesia in young Thoroughbred horses when they are well sedated before induction. A signiicant decrease in HR was reported in horses ater administration of medetomidine 5-10 µg/kg.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…2 Aoki and others reported that the mean induction time in horses premedicated with medetomidine, butorphanol and guaifenesin followed by 1 mg/kg of alfaxalone was 49 seconds. 9 The characteristics of induction in our current study were similar to the results of these previous studies, and the 1 mg/kg of alfaxalone was considered to be an appropriate dose for the induction of anaesthesia in young Thoroughbred horses when they are well sedated before induction. A signiicant decrease in HR was reported in horses ater administration of medetomidine 5-10 µg/kg.…”
Section: Discussionsupporting
confidence: 86%
“…Goodwin and others reported that the mean induction time in colts administered 1 mg/kg of alfaxalone after sedation with acepromazine, medetomidine and guaifenesin was 36 seconds 2 . Aoki and others reported that the mean induction time in horses premedicated with medetomidine, butorphanol and guaifenesin followed by 1 mg/kg of alfaxalone was 49 seconds 9 . The characteristics of induction in our current study were similar to the results of these previous studies, and the 1 mg/kg of alfaxalone was considered to be an appropriate dose for the induction of anaesthesia in young Thoroughbred horses when they are well sedated before induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in desflurane-anesthetized sheep, infusion of alfaxalone at a rate of 0.07 mg/kg/min results in a decrease of desflurane requirements to maintain a surgical depth of anesthesia (Granados et al, 2012). Also, co-administration of a fentanyl CRI (10 µg/kg/h) results in a significant decrease of the alfaxalone infusion rate in dogs (Dehuisser et al, 2017), while combinations with medetomidine (3 -5 µg/kg/h) alone or with either butorphanol (30 µg/kg/h) or guaifenesin (80 mg/kg/h) have been demonstrated to reduce the alfaxalone dose regimen (1.5 -2 mg/kg/h or 0.025 -0.033 mg/kg/min) for TIVA in horses (Goodwin et al, 2013;Ohmura et al, 2016;Aoki et al, 2017). In goats, a significant reduction of the alfaxalone CRI down to 0.02 mg/kg/min has been observed after a combination with either midazolam (0.1 -0.9 mg/ kg/h) or fentanyl (5 -30 µg/kg/h) (Dzikiti et al, 2015;Dzikiti et al, 2016).…”
Section: Figure 2 Graphical Representation (From Top Left To Bottom mentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License recovery times (Adetunji et al, 2002). Smooth inductions and short recovery times are peculiar characteristics of propofol which qualifies it to be used as a constant rate infusion for maintenance of anaesthesia (Aoki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%